Pemeriksaan Setempat dalam Sengketa Pembagian Harta Bersama : Studi Putusan Nomor 4757/Pdt.G/2022/PA.Tgrs - Jeshika Basaria Tambunan; Zakki Adlhiyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to analyze the evidentiary strength of descente in disputes over the division of joint property based on a study of decision number 4757/Pdt.G/2022/PA.Tgrs, as well as examining the judge's considerations in granting a lawsuit based on a study of decision number 4757/Pdt.G/2022/PA.Tgrs. This research uses a normative approach with a case study method. The results of the research show that the strength of descente is independent (vrij bewijsleer), but not binding (dwingend bewijsleer). This means that the results of the descente do not absolutely determine the judge's decision, the judge's decision is still based on a free assessment of all evidence relevant to the case. The judge's considerations in this case stipulate that joint property must be divided fairly, namely that each party is entitled to half of the joint property, as regulated in Article 37 of Law Number 1 of 1974 and Article 97 of the Compilation of Islamic Law. The judge's considerations also show that the principles of justice and legal certainty are a priority, with reference to legal provisions governing the fair distribution of joint property. The decision taken accommodates the interests of both parties, and confirms that the absence of one party in the trial does not prevent decision-making based on the available evidence.